Deciphering the Role of Regulatory CD4 T Cells in Oral and Oropharyngeal Cancer: A Systematic Review - O'Higgins, Caoimhín; Ward, Frank J.; Abu Eid, Rasha (Frontiers in Oncology, 2018)
Background: Recruiting regulatory CD4 T cells (Tregs) into the tumor microenvironment is an important tumor escape mechanism. Diminishing these suppressive cells is therefore one of the targets of cancer immunotherapy. Selective depletion of Tregs has proven successful in enhancing anti-tumor immunity and therapeutic efficacy in multiple tumor types. However, the role of Tregs in oral/oropharyngeal cancers is unclear with conflicting evidence regarding the effect of these suppressive cells on tumor prognosis. In this study, we sought to review the role of Tregs in oral/oropharyngeal cancer with the aim of deciphering the controversy regarding their effect on tumor progression and prognosis. Methods: A systematic review of the literature pertaining to the role of Tregs in oral/oropharyngeal cancer was performed using Scopus, Embase and PubMed. Forty five records were deemed eligible and data describing methodology of Treg detection, tumor type and association with prognosis were extracted. Results: Of the 45 eligible manuscripts accepted for this systematic review, thirty nine studies reported data from human subjects while the remaining studies focused on animal models. Sixteen studies were carried out using peripheral blood samples, while samples from the tumor site were analysed in 18 studies and 11 studies assessed both blood and tumor samples. The transcriptional factor, Foxp3, was the most commonly used marker for Treg identification (38/45). The findings of 25 studies suggested that an increase in Tregs in the tumor microenvironment and/or peripheral blood was associated with poorer prognosis. These conclusions were attributed to the suppression of immune responses and the consequent tumor progression. Conversely, nine studies showed an increase in Tregs in peripheral blood and/or tumor microenvironment was related to a favorable prognosis, particularly in the presence of human papilloma virus, the status of which was only assessed in 11 studies. Conclusions: This review underlines the importance of host immunity in the behavior of oral/oropharyngeal cancer. Furthermore, we report an apparent lack of clarity regarding the true role Tregs play in oral/oropharyngeal cancer progression which could be attributed to inconsistent detection techniques of Tregs. Our results therefore highlight the need for clearer methodologies and more robust phenotyping when defining Tregs.